2006
DOI: 10.1111/j.1528-1167.2006.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Quality of Life Three Years after Temporal Lobectomy: A Controlled Study

Abstract: Summary:Purpose: The goal of epilepsy surgery is not merely to control previously intractable seizures, but also to improve quality of life (QOL). Our goals were to assess, in our Middle Eastern population, the QOL of adults with temporal lobe epilepsy (TLE) 3 years after temporal lobectomy as compared with matched TLE patients who did not undergo surgery and with healthy individuals in the same community.Methods: Twenty consecutive TLE patients who underwent temporal lobectomy 3 years previously were matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 25 publications
4
28
0
2
Order By: Relevance
“…Two studies [40,41] did not find a relation between frequency of seizures and QoL, but all patients in these had symptomatic drug-resistant epilepsy, so the homogenous nature of seizure occurrence might have obscured this relation. Studies that investigated the responsiveness of the QOLIE-31 and other questionnaires, e.g., QOLIE-89 and ESI-55, in patients who had undergone epilepsy surgery or changed drug treatment usually showed a significant improvement of QoL in patients with a marked improvement in seizure frequency and especially in those who became seizure-free [16,25,30,[42][43][44]. Our findings provide further evidence to support the importance of efforts towards the reduction of seizure frequency to improve the QoL.…”
Section: Discussionsupporting
confidence: 58%
“…Two studies [40,41] did not find a relation between frequency of seizures and QoL, but all patients in these had symptomatic drug-resistant epilepsy, so the homogenous nature of seizure occurrence might have obscured this relation. Studies that investigated the responsiveness of the QOLIE-31 and other questionnaires, e.g., QOLIE-89 and ESI-55, in patients who had undergone epilepsy surgery or changed drug treatment usually showed a significant improvement of QoL in patients with a marked improvement in seizure frequency and especially in those who became seizure-free [16,25,30,[42][43][44]. Our findings provide further evidence to support the importance of efforts towards the reduction of seizure frequency to improve the QoL.…”
Section: Discussionsupporting
confidence: 58%
“…1,10,46,49,51,52,60 Several reports have indicated that, in a significant number of patients, seizure tendency can be markedly improved, which may lead to normalization of life in long-term follow-up. 14,16,53 Although it has been reported that invasive diagnostic rt unilat 160 43 30 19 633 54 0 28 967 lt unilat 124 24 18 20 599 21 0 17 823 no. of ops 1 194 60 31 33 1021 43 87 14 1483 2 66 5 12 4 182 31 24 16 680 3 22 3 5 2 31 1 4 10 234 4 5 0 2 0 1 0 0 5 52 total 412 79 78 47 1482 108 147 96 2449 * CC = corpus callosotomy; MST = multiple subpial transection; selAH = selective amygdalohippocampectomy; SSMA = somatosensory motor area.…”
Section: Discussionmentioning
confidence: 99%
“…those with IQ < 70). Surgical ineligibility of controls was not described (N) Altshuler et al (1999) Patients undergoing presurgical evaluation, who did not have surgery for lack of localized seizure focus (12 of 13) or extratemporal focus not suitable for anterior temporal lobe resection (1 of 13) (U) Ommaya (1963) Patients with a diagnosis of temporal lobe epilepsy presenting for surgery, were evaluated and underwent craniotomy, but no removal of brain tissue because of ''lacking focal activity'' (U, S) Penfield and Steelman (1947) Patients operated on 1939-1944 with craniotomy and cortical excision-treatment group (n = 59) versus craniotomy without cortical excision (controls) (n = 16) (U, S) Penfield and Paine (1955) Patients with negative explorations operated on between 1945 and 1950, versus surgery patients (U, S) Vickrey et al (1995) Patients were evaluated for surgery, but not operated on; no identified focus in 42 (91%), two contraindications for surgery, two withdrew from surgery or evaluation (R, U) Markand et al (2000) Patients evaluated for surgery who were considered unsuitable for anterior temporal lobe resections or elected against surgery (R, U) Wiebe et al (2001) Patients were randomized to a delay of presurgical evaluation for 1 year or surgery (W) Yasuda et al (2006) a Medically treated patients with mesial temporal lobe epilepsy followed for more than 12 months (personal communication by the study author), waiting for finishing presurgical evaluation, waiting for surgery after evaluation, or those unsuitable for surgery versus patients undergoing temporal lobe surgery (W, U) Mikati et al (2006) Individually matched patients undergoing presurgical evaluation, who were not eligible for surgery (no single seizure focus, or unacceptable neurologic risk) versus consecutive patients undergoing surgery (75% temporal lobe resections) (U) Bien et al (2006) Patients not eligible for surgery after presurgical assessment (focus not identified, multiple foci, unacceptable neurologic risk) versus surgical patients (W, U) Derry et al (2001) Evaluated but ineligible patients receiving medical management followed for 8.5 years versus surgical patients (U) Jones et al (2002) Individuals who were evaluated for surgery but did not proceed to surgery and were receiving AED treatment versus surgical patients (U) Kumlien et al (2002) Medically treated patients with MRI-verified mesial temporal sclerosis (excluding dual pathology, nonepileptic seizures, nonadherence, uncertain EEG findings) who were considered unsuitable for surgery (no reasons given) versus surgical patients (U) Li (2002) Patients evaluated as surgical candidates who declined surgery or were found otherwise unsuitable for surgery versus surgical patients (U) Moretti Ojemann and…”
Section: Discussionmentioning
confidence: 99%